Stephanie Plum: Fearless Fourteen - Book 14 - Evanovich, Janet (New York : St. Martin's Press, 2008)
Bounty hunter Stephanie Plum and her motley companions--including Grandma Mazur, vice captain Joe Morelli, and Bob the Dog--become entangled in an adventure involving the Burg's premier funeral home and a family pot roast.
Keywords: Fiction